О мультипликаторе группы с нетривиальным центром - Жмудь, Э.М. (Український математичний журнал, 1995)
Продовжуючи дослідження, розпочаті в [1], одержано нерівності, які підсилюють відому нерівність Дж. Гріна для порядку мультиплікатора Шура p-групи. This paper is a sequel of [1]. On the basis of the results obtained therein, we establish inequalities that strengthen the known Green inequality for the order of the Schur multiplier of ap-group.